Bimbingan Belajar Anak Kampung Mbegho Melalui Pendekatan Etnomatematika - Fransiskus Korosando; Manggu Ngguna Raji (Cv. Utility Project Solution, 2023)
Studying from home online during the COVID-19 Pandemic was difficult for the children of Mbegho Village due to limited knowledge among parents, not having an android, and not having textbooks. Learning activities at home are practically impossible. Children tend to choose to play, including playing hazelnut seeds, rather than learn. This empirical condition encourages the writer to carry out mathematics tutoring by utilizing the momentum of the tradition of playing candlenut seeds as a learning medium. This service aims to help 3rd graders from Mbegho Village who have difficulty learning mathematics by partnering with parents, children, and RT.02 Dusun Mbegho, Tomberabu Village 1. Tutoring using the joyful learning method involves 11 children. The results of tutoring at the first meeting were known to be 50% of the eight children reaching a benchmark below 65, with a collective average of 50. The results of tutoring increased significantly at the second meeting; 11 children were able to meet the criteria individually and collectively. In addition, they also obtained: (1) participative values that appear mentally—thoughts, emotions, empathy overcoming difficulties; (2) the value of ethnomathematics as a learning approach that connects local traditions with mathematics; (3) the value of solidarity, or the feeling of being united in carrying out teamwork; and (4) the value of sportsmanship, which appears in obedience to the rules, not justifying any means to win.